Soft polar molecular layers adsorbed on charged nanowire - Lykah, V.A.; Syrkin, E.S. (Condensed Matter Physics, 2004)
A selfconsistent theoretical approach is developed for describing an uncompensated
charge carrier inside a perfect semiconductor quantum wire
covered with a soft molecular layer. Deformation of the molecular layer under
inhomogeneous carrier electric field is described in the model of liquid
crystal with intrinsic electric dipole. The longitudinal quantization of a
charge carrier is reduced to the spectral problem for nonlinear Schrodinger
equation which is solved in terms of elliptic functions. The features of behavior
of the system are as follows: the higher is the interaction, the higher
is the nonlinearity; the lowest quantum levels experience the highest nonlinearity;
the effect should be more pronounced for heavier holes. Under the
increase of interaction the carrier is localized. The occurrence of localized
states could be responsible for the experimentally observed decrease of
conductivity in nanowires. Самоузгоджений теоретичний підхід розроблено для опису незкомпенсованого носія заряда всередені напівпровідникового квантового дроту, що вкритий м’яким молекулярним шаром. Деформація молекулярного шару в неоднорідному електричному полі носія описана в моделі рідкого кристала з власним електричним дипольним моментом. Продольне квантування носія заряда зведено до спектральної проблеми для нелінійного рівняння Шредингера. Самоузгоджене рішення спектральної проблеми отримано в термінах еліптичних функцій. Система має таку поведінку: чим вища взаємодія, тим більша нелінійність; найнижчі квантові рівні відчувають найбільшу нелинійність; ефект має бути більш відчутним для більш важких дірок; при зростанні взаємодії енергетичні рівні знижуються і носій локалізується. Поява локалізованих станів може бути відповідальною за зменшення провідності в нанодротах, що наблодають в експерименті.